Development and validation of structured training module for healthcare workers involved in managing pediatric patients during COVID-19 pandemic using "Objective Structured Clinical Examination" (OSCE) - Rachna Pasi; Thirunavukkarasu Arun Babu; Vinoth Kumar Kalidoss (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: COVID-19 (Coronavirus disease-19) is an ongoing pandemic. COVID vaccine administration in adults has provided some degree of protection from infection but children are still susceptible So, we have to be prepared to handle COVID-19 infection in children by training our healthcare workers by updating both their knowledge and skills. We developed a training module to train our healthcare workers in all domains of learning and also planned related assessment methods to know the effectiveness of the module. MATERIALS AND METHODS: This was a quasi-experimental study with pre- and post-intervention conducted at a tertiary-level teaching medical college in southern India from July to September 2021. The training module was developed as per the "ADDIE" model of the development process module. It was further validated by five experts before implementation. In addition to the quasi-experimental method of evaluation like pre- and post-test, Observed Skill clinical examination (OSCE) had been also used as an assessment tool at the completion of training. A total of 92 participants have been trained as per this module in our tertiary-level care hospital. The association between continuous and categorical variables was assessed using an independent t-test and ANOVA, and paired t-test was used for comparing the difference between pre- and post-test scores. RESULTS: Pre-test scores had no association with years of experience (P = 0.803) and previous training status of participants (P = 0.350). The mean difference of pre- and post-test scores was 3.8 and it was statistically significant (P value < 0.001) A weak positive correlation between pre- and post-test was present by the Spearmen correlation test (r = 0.337). The correlation between post-test score and OSCE score does not have a significant correlation. CONCLUSION: Structured training module was effective in training the participants. Multimode assessment method (Pre-test, Post-test, and OSCE) is an important step to evaluate any training program as compared to only the pre- and post-test methods of evaluation.